Contradições e descontinuidades nos sistemas de atividade do transporte aéreo brasileiro : restrições às viagens e as estratégias de passageiros com deficiência, idosos e obesos - Silva, Talita Naiara Rossi da (2016)
Global phenomena such as population aging, increased rate of disability, and growing numbers of obese people have gained intense attention within the air transportation industry since it expects increases in travel and changes in the profile of users. However, studies have indicated gaps between the needs of passengers and the services and assistance provided by airlines and airports. Therefore, the objective of this study was to understand the contradictions and discontinuities in the activity systems of passengers with disability, elderly and obese in the Brazilian air transportation originating restrictions to participation during the flight and during the boarding and deplaning process of air travel. In the present study, a qualitative approach was adopted based on Ergonomics and the Activity Theory. The research participants were passengers with physical, visual, and auditory disabilities and elderly and obese passengers. A combination of methods and techniques was used for data collection, including: 14 preliminary interviews in health care organizations and facilities that provide assistance and services for the participant groups and air transportation users, with a total of 25 participants; a questionnaire survey involving 399 respondents; and observations in commercial aviation. A total of 43 non-participant observations were carried out, and other eight participant observations took place during the journey, which included two self-confrontation interviews. The results indicated passenger participation restrictions during the journey affect attitudinal barriers and limited spatial accessibility that are related to airport infrastructure, airport signs, operational factors, equipment, aircrafts, and regulatory aspects. These restrictions are related to contradictions in the interaction of the components of activity system, which include: the passenger, the artifacts, the rules, the community (passengers and workers), the airport operators, and the airlines, and the object of the activity. It was found that, in order to face these difficulties, passengers employ personal and interpersonal strategies. Therefore, specifications were developed to change the contextual factors associated with the environment, equipment, and operations. To promote full participation during the air journey, some changes are needed; primarily transformation in significance and representations for action of people involved in the air transportation and their work activity, seeking to achieve integration between design and use. This study was carried out focusing on the activity, which contributed to the involvement of different social actors; thus the information provided is based on the learning gained from experience and interaction with the subjects and the context aiming to demonstrate the users’ needs and constraints and support new air transport developments.